Research of the activity of local anesthetics and antiseptics regarding clinical isolates of Acinetobacter baumannii as pathogens of postoperative infectious complications - Nazarchuk, Oleksandr; Dmyrtriiev, Dmytro; Babina, Yuliana; Faustova, Mariia; Burkot, Vita (Acta Biomedica Atenei Parmensis, 2022)
Background. About 60% of all nosocomial infections are caused by microorganisms found in biofilms. Acinetobacter baumannii, as a pathogen of nosocomial infections, occur more frequently in surgical hospitals. The aim of the study was to study the in vitro formation of A. baumannii monotype biofilms under the influence of local anesthetics and antisepticsMaterials and methods. The antimicrobial activity of local anesthetics (0.25-0.5%, bupivacaine, 2.0% lidocaine, 0.75% ropivacaine) and antiseptics (decamethoxine 0.1%, octenidine 0.1%, chlorhexidine 0.05%) ) against clinical strains of A. baumannii and studied their ability to produce biofilms.Results. The bacteriostatic effect of local anesthetics on A. baumannii within the current concentrations of these drugs, which provide analgesic effect, has been proven. The given results indicate that A.baumanni cultures have a pronounced ability to form biofilms. Clinical strains of opportunistic microorganisms A. baumannii circulating in the hospital environment are highly sensitive to antiseptics decamethoxine and octenidine, chlorhexidine has a weak bactericidal effect against acinetobacteria. The results of studying the effect of local anesthetics on the process of formation of the strain "young" biofilms showed the presence of a dose-dependent effect. The greatest inhibitory activity against "young" biofilms was detected under the combined action of the antiseptic decamethoxine (in concentrations, not exceeding 3.9 μg / ml) and anesthetics (OD-0,199-0,223) (p